2019
DOI: 10.7554/elife.49388
|View full text |Cite
|
Sign up to set email alerts
|

The yellow gene influences Drosophila male mating success through sex comb melanization

Abstract: Drosophila melanogaster males perform a series of courtship behaviors that, when successful, result in copulation with a female. For over a century, mutations in the yellow gene, named for its effects on pigmentation, have been known to reduce male mating success. Prior work has suggested that yellow influences mating behavior through effects on wing extension, song, and/or courtship vigor. Here, we rule out these explanations, as well as effects on the nervous system more generally, and find instead that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 70 publications
1
62
1
Order By: Relevance
“…Interestingly, an early report suggested that e mutants of D. melanogaster were more resistant to desiccation stress than wildtype flies, whereas y mutants of multiple species were less desiccation resistant (Kalmus 1941). In addition, e mutants produce longer hydrocarbon cuticle chains (Massey et al 2019a), whereas male y mutants have difficulty to sustain copulation (Massey et al 2019b), underscoring the pleiotropic function of these genes. It was shown independently that selection in the laboratory for desiccation resistance produced populations with longer hydrocarbon chains (Gibbs et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an early report suggested that e mutants of D. melanogaster were more resistant to desiccation stress than wildtype flies, whereas y mutants of multiple species were less desiccation resistant (Kalmus 1941). In addition, e mutants produce longer hydrocarbon cuticle chains (Massey et al 2019a), whereas male y mutants have difficulty to sustain copulation (Massey et al 2019b), underscoring the pleiotropic function of these genes. It was shown independently that selection in the laboratory for desiccation resistance produced populations with longer hydrocarbon chains (Gibbs et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our estimations of homing rates by the shadow drive in white locus are notably higher than the previously reported in yellow locus: 59-72% ( Figure 2) vs. 29-32% (Guichard et al 2019) and 38% (Champer et al 2019c), although the ratio of first generation drive to shadow drive frequencies is comparable in these systems ($50%). The differences may be due to the yellow locus being less accessible to cleavage and HDR than white locus, or perhaps the lower fitness of yellow LOF somatic mutations (see below) biases against their inheritance (Massey et al 2019).…”
Section: Somatic Expression Of Cas9 Results In High Mutagenesis Ratesmentioning
confidence: 99%
“…S2; Supplementary Table S2). To activate CasRx expression in specific tissues, we used available Gal4 driver lines that restricted expression to either the eye (GMR-Gal4) 46 or the wing and body (yellow-Gal4); 47 ( Supplementary Table S2). These lines were crossed to the same homozygous gRNA array lines described above targeting w, y, or N ( Supplementary Fig.…”
Section: Programmable Rna Targeting Of Endogenous Target Genesmentioning
confidence: 99%